2018
DOI: 10.1371/journal.pone.0198924
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the Geenius HIV 1/2 Confirmatory Assay and the HIV-1 and HIV-2 Western blots in the Japanese population

Abstract: Accurate diagnosis of earlier HIV infection is essential for treatment and prevention. Currently, confirmation tests of HIV infection in Japan are performed using Western blot (WB), but WB has several limitations including low sensitivity and cross-reactivity between HIV-1 and HIV-2 antibodies. To address these problems, a new HIV testing algorithm and a more reliable confirmation and HIV-1/2 differentiation assay are required. The Bio-Rad Geenius HIV-1/2 Confirmatory Assay (Geenius) has recently been approved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…While false positive HIV tests occasionally occur, both the ARCHITECT® and ADVIA Centaur® Ag/Ab are robust screening assays and have reported specificity of over 99% [10][11][12]. The Bio-Rad Geenius™ confirmatory assay has been evaluated for HIV-1 and HIV-2 confirmatory testing and discrimination in a variety of populations [8,[13][14][15][16]. The manufacturer's instructions provided with the test claim over 99% specificity, however the results of studies in target populations vary with specificity reported to be between 93 and 99% [8,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…While false positive HIV tests occasionally occur, both the ARCHITECT® and ADVIA Centaur® Ag/Ab are robust screening assays and have reported specificity of over 99% [10][11][12]. The Bio-Rad Geenius™ confirmatory assay has been evaluated for HIV-1 and HIV-2 confirmatory testing and discrimination in a variety of populations [8,[13][14][15][16]. The manufacturer's instructions provided with the test claim over 99% specificity, however the results of studies in target populations vary with specificity reported to be between 93 and 99% [8,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Abbate et al [ 11 ] and Wong et al [ 12 ] reported that the sensitivity of the test for acute HIV-1 infection was low. Kondo et al reported that seven of 20 specimens from the acute phase of HIV-1 infection were identified as HIV-1-positive [ 13 ]. In addition, two of 130 HIV-negative specimens and two of 10 Determine HIV-1/2 (Alere Medical, Chiba, Japan)-positive and HIV-1 nucleotide amplification test-negative (HIV pseudo-positive) specimens cross-reacted with HIV-1-specific lines [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WB assay detects the HIV-1 antibodies that bind to fixed HIV-1 proteins. Globally, it is the most commonly used method for clinical confirmation of HIV-1 infection (Centers for Disease Control [CDC], 2014; Liu et al, 2016; Kondo et al, 2018) and positive WB result is a prerequisite for antiretroviral therapy and laboratory follow-up including CD4 count and HIV-1 viral load test in many low- and middle-income countries. Although HIV-1 nucleic acid testing (NAT) has been recommended for HIV-1 screening, particularly for individuals with acute HIV-1 infection and late-stage AIDS (Tang et al, 2008; Patel et al, 2012; Centers for Disease Control [CDC], 2014; Liu et al, 2016), it is not commonly used for diagnosis due to its cost and technology threshold.…”
Section: Discussionmentioning
confidence: 99%